ILLOCUTIONARY ACTS IN CAPTIONS USED BY TUNJUNGAN PLAZA’S OFFICIAL INSTAGRAM ACCOUNT IN END OF YEAR POSTS 2018 - Chandra, Daniel (Seminar Nasional Ilmu Terapan, 2019)
Social media nowadays have become a part of people’s everyday lives. Its growth makes the great involvement of marketing business activities such as promoting brands/product which use Instagram as their social media platform. For many, the problem of using Instagram is about confusion of creating interesting caption to attract follower’s attention and even their purchase intention. Therefore, this study aims to give the deep understanding related to advertising in the eye of speech acts’ perspective especially the role of illocutionary acts in captions and its function in Instagram. The main object of analysis in this study was official instagram account of Tunjugan Plaza (@tunjungan_plaza). Furthermore, this study applied the exploratory sequential design which shows sequential collection of qualitative and quantitative data. The results found that there were four types of illocutionary acts used by @tunjungan_plaza in end year posts such as Representatives, Directives, Commissives, and Expressives. Among them, the most frequently used were Directives and Commissives and there was also the positive influence of them towards the Purchase Intention of @tunjungan_plaza’s follower. Thus, the result can be considered to apply in creating interesting caption related to the advertisement goals.